2013
DOI: 10.1007/s40266-013-0107-7
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Antiretrovirals, and Adherence: A Meta Analysis of Adherence among Older HIV-Infected Individuals

Abstract: Introduction Older adults are generally considered to be at greater risk for medication non-adherence due to factors such as medication complexity, side effects, cost, and cognitive decline. However, this generalization may not apply to older adults with human immunodeficiency virus (HIV). Regardless of age, suboptimal adherence to antiretroviral therapy (ART) can lead to increased viral load, immunosuppression, drug-resistant viral strains, co-morbidities, and opportunistic infections. Understanding trends of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 46 publications
10
97
4
Order By: Relevance
“…24 Similarly, a recent systematic review and meta-analysis noted that older age reduced the risk of ART non-adherence by 27% (relative risk 0.72, [0.64, 0.82]). 25 These studies suggest that differences in ART adherence between older and younger adults exist and may mediate the relationships with viral suppression. Unfortunately, ART adherence data was unavailable and thus was not included in our analyses.…”
Section: Discussionmentioning
confidence: 95%
“…24 Similarly, a recent systematic review and meta-analysis noted that older age reduced the risk of ART non-adherence by 27% (relative risk 0.72, [0.64, 0.82]). 25 These studies suggest that differences in ART adherence between older and younger adults exist and may mediate the relationships with viral suppression. Unfortunately, ART adherence data was unavailable and thus was not included in our analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Studies from high‐income countries and resource‐limited settings have also shown higher rates of virologic suppression among older patients as a result of better treatment adherence compared to younger patients 12, 33, 36, 37, 38. Possible explanations for a higher mortality risk in older patients include multi‐morbidities, polypharmacy, chronic infection with viral pathogens (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73][74][75][76][77] Interestingly, this finding is not explained by differences in virological response, as older HIV-infected patients tend to have a superior virological outcome when compared with younger patients. [78][79][80][81][82][83] Some suggests that these finding may be linked with higher adherence in older patients, 78,[84][85] but other authors reported a higher risk of inadequate adherence in HIV patients who have other comorbidities and take other medications besides HAART. [86][87] While virological response seems not to be influenced by age, at least biologically, older patients have lower CD4C T-cell gain compared with younger persons, [88][89][90][91][92][93][94][95] even when adjusted for antiretroviral therapy regimens.…”
Section: Clinical Outcomementioning
confidence: 99%